Does ICT-integration in elementary accounting education motivate students' learning? - Tan, Boon See; Salleh, Arfah (Malaysian Educational Technology Association, 2007)
This paper examines the extent to which the new pedagogical practice which integrated ICT into the SPM, Principles of Accounting (Prinsip Perakaunan) subject, is able to motivate students’ learning. The research was conducted based on the Ministry of Education, Malaysia pre-pilot project in 10 national and technical secondary schools in Kelantan under the first phase of the international and professional benchmarking project. To facilitate the teaching and learning process under the new ICT-based environment, copies of a newly developed lesson plan for the subject which incorporates the use of ICT including the ASSETBase software in the classroom were distributed to the accounting teachers. Students’ responses to this novel pedagogical attempt and their perception of teachers’ performance were assessed through interviews with close and open-ended questions. The findings indicate that the new ICT-based pedagogical approach was able to create students’ interest in the subject. Students too, believed that they were able to understand the subject and were confident that they would perform well through this new approach of learning. The Pearson correlation analysis results show that students’ interest, perceived understanding and performance confidence were significantly correlated to students’ perception of teachers’ attitude. In addition, students’ ability to understand is found to be significantly correlated to their perception of teachers’ preparedness for the class. Students’ interest is also significantly correlated to their interaction in the classroom.